2008
DOI: 10.4062/biomolther.2008.16.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacological Profile of the Water Extract of Gardenia jasminoides and Its Constituents, Genipin and Geniposide, in Mice

Abstract: − Gardenia jasminoides (G. jasminoides) is traditionally used to treat insomnia, jaundice, emotional disorders, hepatic disease, and inflammatory disease. Previously, we found that geniposide and the water extract of G. jasminoides increased Cl -influx in neuroblastoma. Here we examined the psychopharmacological activities of G. jasminoides and its constituents. G. jasminoides extract was orally administered at 100 and 200 mg/kg, and genipin and geniposide were intraperitoneally injected at 2, 10, and 20 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In terms the other psychoactive component geniposide, however, its content was almost constant even before fruit development. Earlier study by Choi and co-workers 27 indicated that geniposide exerted the increase in Clinflux in neuroblastoma, resembling GABA-ergic activation. Taking this data into consideration, one may further suggest that geniposide could be the component of the extract used in our present study, responsible for the sleep-improving effect, as crocin has been shown to be absent at the flowering stage.…”
Section: Discussionmentioning
confidence: 87%
“…In terms the other psychoactive component geniposide, however, its content was almost constant even before fruit development. Earlier study by Choi and co-workers 27 indicated that geniposide exerted the increase in Clinflux in neuroblastoma, resembling GABA-ergic activation. Taking this data into consideration, one may further suggest that geniposide could be the component of the extract used in our present study, responsible for the sleep-improving effect, as crocin has been shown to be absent at the flowering stage.…”
Section: Discussionmentioning
confidence: 87%
“…Choi et al. 213 subjected ICR mice to different behavioral tests after orally administering 100 and 200 mg/kg doses of G. jasminoides fruit, as well as intraperitoneally injecting both genipin and geniposide, at doses of 2–20 mg/kg, for 1 week. The control group was administered with saline solution, while the positive control group was administered with diazepam.…”
Section: Chinese Medicinal Plantsmentioning
confidence: 99%